Relationship between Upper Quarter Y Balance Test performance and throwing proficiency in adolescent Olympic handball players - Bauer, J.; Schedler, S.; Fischer, S.; Muehlbauer, T. (BMC Sports Science, Medicine and Rehabilitation, 2020)
Background: Olympic handball is a sport mainly focused on executing throwing and passing techniques with the throwing arm. Functional specialization due to the unilateral characteristic and dominance of the throwing arm may lead to adapted control of shoulder stability and mobility. Thus, we examined side differences between the throwing and the non-throwing arm. Additionally, correlations between the Upper Quarter Y Balance Test (YBT-UQ) and handball-specific performance measures were investigated. Methods: All participants (F = 13 yrs., n = 14, training experience [te] 5.9 ± 1.3 yrs.; M = 14 yrs., n = 24, te 6.5 ± 2.5 yrs.; M = 15 yrs., n = 18, te 9.3 ± 2.2 yrs) were Olympic handball players of a regional youth selection team. YBT-UQ was executed assessing performance in medial, inferolateral and superolateral reach direction normalized to the upper limb length together with a composite score of the mean of all reach directions. A radar gun and a target net were used for the assessment of throwing velocity and throwing accuracy. The paired t-test was used to detect side differences in YBT-UQ performance. Pearson`s correlation analysis was calculated for associations between YBT-UQ and throwing velocity/accuracy. Results: Significant differences between the throwing and non-throwing arm were only detected for the superolateral reach direction in the 14-year-old males. Small correlations between YBT-UQ performance and throwing velocity/accuracy (13-year-old females: - 0.01 = r = - 0.37 / 0.01 = r = 0.31; 14-year-old males: 0.10 = r = 0.45 / -0.01 = r = .-0.51; 15-year-old males: 0.06 = r = 0.34 / 0.01 = r = - 0.45) were observed, irrespective of age and sex category. Conclusions: There was only a minimal difference in performance of the YBT-UQ between the throwing and non-throwing arm and only weak if any relationships between throwing performance and stability/mobility of the upper extremities in adolescent Olympic handball players existed. Further research is needed to investigate whether the YBT-UQ is a useful tool to detect training-related improvements in measures of shoulder stability/mobility and functional performance.